A program based on reflective teaching for developing student-teachers' competency and their pupils achievements - مي احمد السيد (Faculty of Education - Port Said University, 2023)
The theoretical and conceptual framework of the present study is based on Tice's (2002) concept of reflective teaching and Richards and Farrell's (2005) of language teacher's professional development. The present study discussed the impact of reflective teaching on developing the trainee-teachers' teaching competency on the one hand and on developing the FL achievement of their pupils on the other. There are two types of participants who took part in the present study. One hundred third year student-teachers enrolled at the Department of English, Faculty of Education, October 6 University. In addition, 30 primary school pupils, who were taught by the 100 hundred student-teachers during the latter teaching practice, also participated in the present study. One way analysis of variance (ANOVA) was conducted twice to determine statistical differences between the student-teachers' responses to the pre and post-administrations of the reflective teaching questionnaire and between their pupils' achievements in the pre and post language tests. The study introduced pedagogical implications to integrate the reflective teaching with the teaching practice syllabus for English Department students, Faculty of Education, October 6 University.